3. TWO RARE CASES OF ECTOPIC PREGNANCY: CASE REPORTS (Vietnam Journal of Community Medicine, 2026)
Ectopic pregnancy is a leading cause of maternal mortality in the first trimester. Among its uncommon forms, abdominal pregnancy and heterotopic pregnancy are particularly challenging to diagnose and are easily overlooked. We report two illustrative cases diagnosed and managed at Transport Hospital, with the aim of enhancing awareness and clinical decision-making among obstetricians
Keywords: ectopic pregnancy; abdominal pregnancy; heterotopic pregnancy; laparoscopy; early diagnosis